Broadband‐acre City: 'No Traffic Problem, No Buffering'. (3rd January 2023) - White, Marcus; Glackin, Stephen
Abstract: The global pandemic and consequent lockdowns have provoked an evacuation of workplaces and urban centres. For society to continue to function, there has been a massive movement towards home working enabled by Teams and Zoom. This has ramifications on not just our lives but also digital infrastructure, commerce and entertainment, as well as a myriad of other dynamics, all of which has totally reconfigured our lifestyles and health in recent years. Stephen Glackin, Senior Research Fellow at the Centre for Urban Transitions at Swinburne University of Technology in Melbourne, and Guest‐Editor Marcus White, discuss this spatial revolution.